Аrtistic features of Zhanat Askerbekkyzy’s poetry - Kurmambayeva К.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article provides a comprehensive scientific analysis of the poems of Zhanat Askerbekkyzy. The romantic harmony of Zhanat Askerbekkyzy’s poems is compared with the poetry of Oralkhan Bokey. Among the talented youth who entered Kazakh poetry in the 1990s, Zhanat stands out as a poet with a distinctive, unique style. The author of the article reveals symbolic and lyrical images in the poems of Zhanat Askerbekyzy. In addition to lyrical stanzas, the author of the article analyzes and systematizes on specific examples of the use of patriotic motives in the poems of Zhanat Askerbekyzy. The author also scientifically expounds the fact that the poet often added elements of mythology and folklore to his poems. The author purposefully has studied the novelty of Zhanat Askerbekyzy’s poetry. Where appropriate, the author used research by scholars published in the field of literary criticism in writing the article. The poet’s poems have explored his national style, artistry and aesthetic taste, and have revealed the poet’s own handwriting. The poet’s ability to defend ethno-cultural values, to reveal national traditions and thereby contribute to Kazakh poetry is analyzed and explained. In her article, the author of the article was able to show that the language and style of the poems are clear.